The impact of COVID-19 non-pharmaceutical interventions on the lived experiences of people living in Thailand, Malaysia, Italy and the United Kingdom: A cross-country qualitative study. - Mira L Schneiders; Bhensri Naemiratch; Phaik Kin Cheah; Giulia Cuman; Tassawan Poomchaichote; Supanat Ruangkajorn; Silvia Stoppa; Anne Osterrieder; Phee-Kheng Cheah; Darlene Ongkili; Wirichada Pan-Ngum; Constance R S Mackworth-Young; et al. (PLoS ONE)
This qualitative study explores the impact of non-pharmaceutical interventions (NPIs), including social distancing, travel restrictions and quarantine, on lived experiences during the first wave of the COVID-19 pandemic in Thailand (TH), Malaysia (MY), Italy (IT) and the United Kingdom (UK). A total of 86 interviews (TH: n = 28; MY: n = 18; IT: n = 20; UK: n = 20) were conducted with members of the public, including healthcare workers (n = 13). Participants across countries held strong views on government imposed NPIs, with many feeling measures lacked clarity. Most participants reported primarily negative impacts of NPIs on their lives, including through separation, isolation and grief over missed milestones; work-related challenges and income loss; and poor mental health and wellbeing. Nonetheless, many also experienced inadvertent positive consequences, including more time at home to focus on what they most valued in life; a greater sense of connectedness; and benefits to working life. Commonly employed coping strategies focused on financial coping (e.g. reducing spending); psycho-emotional coping (e.g. engaging in spiritual practices); social coping and connectedness (e.g., maintaining relationships remotely); reducing and mitigating risks (e.g., changing food shopping routines); and limiting exposure to the news (e.g., checking news only occasionally). Importantly, the extent to which participants' lived experiences were positive or negative, and their ability to cope was underpinned by individual, social and economic factors, with the analysis indicating some salient differences across countries and participants. In order to mitigate negative and unequal impacts of NPIs, COVID-19 policies will benefit from paying closer attention to the social, cultural and psychological-not just biological-vulnerabilities to, and consequences of public health measures.